Deteksi Area Parkir Mobil Berbasis Marker Menggunakan Moment Invariants dan K-NN - Kristian Adi Nugraha (Maranatha University Press, 2019)
Smart car parking system has become very important these days because it is very helpful and saves a lot of time to find a parking spot. However, the installation of that system is too expensive, then not everyone can afford it. Affordable solution for car parking spot detection can be implemented using installed camera or CCTV combined with computer vision method. New problem appears if the camera position is limited like indoor building causing one marker shape can be captured in different shape due to the different camera angle. In this work, I do a research to detecting marker using moment invariant method. Even the shape of marker changed a little, moment invariant method can still recognize that shape with overall accuracy 91.94%.